The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1038/ijo.2013.196
|View full text |Cite
|
Sign up to set email alerts
|

Improved acylated ghrelin suppression at 2 years in obese patients with type 2 diabetes: effects of bariatric surgery vs standard medical therapy

Abstract: OBJECTIVE Roux-en-Y gastric bypass (RYGB) produces more durable glycemic control than sleeve gastrectomy (SG) or intensive medical therapy (IMT). However, the contribution of acylated ghrelin (AG), a gluco-regulatory/appetite hormone, to improve glucose metabolism and body composition in patients with type 2 diabetes (T2D) following RYGB is unknown. DESIGN STAMPEDE (Surgical Treatment and Medication Potentially Eradicate Diabetes Efficiently) was a prospective, randomized controlled trial. SUBJECTS Fifty-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 44 publications
2
40
0
Order By: Relevance
“…As expected, sleeve gastrectomy reduced desacyl ghrelin levels, due to the resection of the gastric fundus, the major production site of the hormone15. By contrast, plasma acylated ghrelin remained unchanged after bariatric surgery, which is in accordance with other authors2641, and the acylated/desacyl ghrelin ratio increased, suggesting an enhanced post-transcriptional modification in order to maintain the circulating levels of the acylated hormone. In a previous work of our group, we found that both acylated and desacyl ghrelin stimulated intracellular lipid accumulation in human differentiated omental adipocytes through the upregulation of PPARγ and SREBP-1c and other fat-storage related molecules20.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As expected, sleeve gastrectomy reduced desacyl ghrelin levels, due to the resection of the gastric fundus, the major production site of the hormone15. By contrast, plasma acylated ghrelin remained unchanged after bariatric surgery, which is in accordance with other authors2641, and the acylated/desacyl ghrelin ratio increased, suggesting an enhanced post-transcriptional modification in order to maintain the circulating levels of the acylated hormone. In a previous work of our group, we found that both acylated and desacyl ghrelin stimulated intracellular lipid accumulation in human differentiated omental adipocytes through the upregulation of PPARγ and SREBP-1c and other fat-storage related molecules20.…”
Section: Discussionsupporting
confidence: 87%
“…Circulating ghrelin concentrations decrease after sleeve gastrectomy due to the resection of the gastric fundus15 with RYGB additionally suppressing post-prandial ghrelin levels26. The aim of the present study was to analyze in diet-induced obese rats the implication of ghrelin isoforms in the improvement of hepatosteatosis after sleeve gastrectomy, a restrictive bariatric surgery procedure.…”
mentioning
confidence: 97%
“…It has been hypothesized that LSG results in acute alterations to the regulation of appetite and mechanical function of the gut, both directly via excision of the greater curvature of the stomach, and indirectly through downstream endocrine and nutrient processing changes, all of which act to promote prolonged weight reduction [5]. Prior studies have demonstrated decreased levels of leptin and ghrelin [10, 11] and increased GLP-1 [12] following LSG, but much less is known about other molecular factors implicated in the regulation of blood-glucose homeostasis, gastric function, and emerging markers of adiposity. Additionally, many studies have sought to measure these hormones as surrogate markers of efficacy to evaluate LSG compared to other bariatric techniques [13], rather than to ascertain the mechanism of action of LSG.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the anti-diabetic effect of surgery is present prior to significant weight loss, indicating that the anatomical circumvention or manipulation per se is the underlying contributor to T2DM remission [13][14][15]. Altered secretion of gastrointestinal hormones such as glucagon-like peptide 1 (GLP-1), ghrelin and gastrin has been attributed to the rapid postoperative improvement in glycemic control [16][17][18]. All these hormones regulate pancreatic BCM in preclinical studies [19][20][21].…”
mentioning
confidence: 97%